Scientific Production on the Social Economy: A Review of Worldwide Research - Macías Ruano, Antonio José (Voluntas, 2021)
The aim of this article is to assess the use of the term Social Economy, while being aware of its lack of concreteness, and to analyze the level of scientific production by means of a bibliometric analysis using WoS (JCR) and Scopus (SJR) as sources. Starting in 2004 and related to the Charter of Principles of the Social Economy, the material development of articles began. The most receptive countries are Spain, the USA, China, the UK and Canada. In terms of the most productive journals, Voluntas in JCR and CIRIEC-Spain and REVESCO in SJR stand out. Scientific production on this issue is linked to university institutions, namely the Chinese Academy of Sciences, the University of Valencia and the University of Quebec. The most prevalent subject are Economics and Business in the case of JCR and Social Sciences in SJR. The most recognized term is that of cooperatives and the most prevalent keyword trends being related to sustainable development, climate change, urbanization, management and China.